2019
DOI: 10.1093/humupd/dmz036
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic health in offspring of women with PCOS compared to healthy controls: a systematic review and individual participant data meta-analysis

Abstract: BACKGROUND Women diagnosed with polycystic ovary syndrome (PCOS) suffer from an unfavorable cardiometabolic risk profile, which is already established by child-bearing age. OBJECTIVE AND RATIONALE The aim of this systematic review along with an individual participant data meta-analysis is to evaluate whether cardiometabolic features in the offspring (females and males aged 1–18 years) of women with PCOS (OPCOS) are less favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 73 publications
0
43
0
1
Order By: Relevance
“…( 8 , 75 ). Altogether, endocrine and metabolic events in intrauterine life become evident early postnatally ( 76 ) and may give origin to a high rate of overt signs and symptoms of PCOS manifesting at puberty and progressing with age ( 77 ). Apart from subtle signs of a compromised cardiometabolic health, predominantly in female offspring ( 76 ) the diagnosis of PCOS in mothers and/or elevated fetal testosterone has been also linked to pervasive developmental disabilities, autism spectrum disorder, and attention-deficit/hyperactivity disorder, an evidence recently confirmed in a US cohort of infants of PCOS mothers ( 78 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 8 , 75 ). Altogether, endocrine and metabolic events in intrauterine life become evident early postnatally ( 76 ) and may give origin to a high rate of overt signs and symptoms of PCOS manifesting at puberty and progressing with age ( 77 ). Apart from subtle signs of a compromised cardiometabolic health, predominantly in female offspring ( 76 ) the diagnosis of PCOS in mothers and/or elevated fetal testosterone has been also linked to pervasive developmental disabilities, autism spectrum disorder, and attention-deficit/hyperactivity disorder, an evidence recently confirmed in a US cohort of infants of PCOS mothers ( 78 ).…”
Section: Introductionmentioning
confidence: 99%
“…7 Women with PCOS have been shown to be at increased risk of metabolic disease including type 2 diabetes mellitus (T2DM), nonalcoholic fatty liver disease (NAFLD), and cardiovascular disease (CVD). 8 Most studies on PCOS have focused on classic C 19 androgens, their precursors and/or their downstream urinary metabolites for biochemical assessment of androgen excess. However, the newly described, adrenal-derived C11-oxy C 19 androgen subclass is emerging to be clinically and biochemically significant in the context of PCOS-related Implicating androgen excess in propagating metabolic disease in polycystic ovary syndrome androgen excess.…”
Section: Introductionmentioning
confidence: 99%
“…8 Most studies on PCOS have focused on classic C 19 androgens, their precursors and/or their downstream urinary metabolites for biochemical assessment of androgen excess. However, the newly described, adrenal-derived C11-oxy C 19 androgen subclass is emerging to be clinically and biochemically significant in the context of PCOS-related Implicating androgen excess in propagating metabolic disease in polycystic ovary syndrome androgen excess. 9 In our recent study, we found that C11-oxy C 19 androgens are the majority of circulating serum androgens in women with PCOS 10 , thus emphasising the importance of improving our understanding of the impact of both classic and C11-oxy C 19 androgens on women's health.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations